स्वातन्त्र्यवीराः - (:unkn) unknown (Kavikulguru Kalidas Sanskrit Vishwavidyalaya Ramtek Nagpur Maharashtra, 2004)
This is a Bal sahitay in Sanskrit. The biography of Rani Lakshmibaie, Bhagat Singh, Sawarkar, Netaji Subhash Chandra Bose, Sardar UdhamSingh, Wasudev Balwant Fadke is given in this book.
Swatantryavirah
Keywords: Children's literature; Sanskrit